2022
DOI: 10.1186/s13012-022-01192-w
|View full text |Cite
|
Sign up to set email alerts
|

Extending analytic methods for economic evaluation in implementation science

Abstract: Background Economic evaluations of the implementation of health-related evidence-based interventions (EBIs) are conducted infrequently and, when performed, often use a limited set of quantitative methods to estimate the cost and effectiveness of EBIs. These studies often underestimate the resources required to implement and sustain EBIs in diverse populations and settings, in part due to inadequate scoping of EBI boundaries and underutilization of methods designed to understand the local contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…Thoughtfully considering how prior literature can inform future decision-making in different contexts is thus core to any decision analysis, and all inputs used throughout a decision analysis should be interrogated and justified [73]. One major area of current focus with implementation science that is often missing detail is the costs of implementation [74][75][76][77]. Recent publications by the "Economics and Cost" action group of the Consortium for Cancer Implementation Science have set out definitions, guidance, methods, and best practices for understanding the costs of implementation and conducting economic evaluations in implementation science [36,74,[77][78][79][80] and complement ongoing work in the field [6,8,12,14,61,75,76,[81][82][83][84].…”
Section: Improve Reporting and Transparency Of Cost Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Thoughtfully considering how prior literature can inform future decision-making in different contexts is thus core to any decision analysis, and all inputs used throughout a decision analysis should be interrogated and justified [73]. One major area of current focus with implementation science that is often missing detail is the costs of implementation [74][75][76][77]. Recent publications by the "Economics and Cost" action group of the Consortium for Cancer Implementation Science have set out definitions, guidance, methods, and best practices for understanding the costs of implementation and conducting economic evaluations in implementation science [36,74,[77][78][79][80] and complement ongoing work in the field [6,8,12,14,61,75,76,[81][82][83][84].…”
Section: Improve Reporting and Transparency Of Cost Datamentioning
confidence: 99%
“…One major area of current focus with implementation science that is often missing detail is the costs of implementation [74][75][76][77]. Recent publications by the "Economics and Cost" action group of the Consortium for Cancer Implementation Science have set out definitions, guidance, methods, and best practices for understanding the costs of implementation and conducting economic evaluations in implementation science [36,74,[77][78][79][80] and complement ongoing work in the field [6,8,12,14,61,75,76,[81][82][83][84].…”
Section: Improve Reporting and Transparency Of Cost Datamentioning
confidence: 99%
“…For instance, cognitive behavioral therapy for insomnia is generally not well‐reimbursed but is preferred over hypnotic medications due to concerns over falls and other adverse events 39,40 . Investigators should include a health economist on the research team to ensure reasonable assumptions and cost‐analysis approaches are reported 41,42 …”
Section: Implementation Science Barriers For Geriatrics Researchersmentioning
confidence: 99%
“…39,40 Investigators should include a health economist on the research team to ensure reasonable assumptions and cost-analysis approaches are reported. 41,42…”
Section: Stari Outcomesmentioning
confidence: 99%
“…Information about the human resource needs and costs for PrEP provision can help identify and close potential staffing and financing gaps. Time-and-motion studies are a tool to assess human resource needs and optimize work processes [ 7 ]. We conducted a time-and-motion study to observe and record how health care workers (HCWs) spent time on the provision of PrEP activities during a PrEP demonstration project in Eswatini.…”
Section: Introductionmentioning
confidence: 99%